2020
DOI: 10.1177/2158244020962758
|View full text |Cite
|
Sign up to set email alerts
|

Training Needs of Academics on Inclusive Education and Disability

Abstract: The aim of this article is to analyze, from the academic staff’s perspective, the training needs they require to provide an inclusive education to students with disability. Academics from a Spanish university participated in this research. We used a qualitative methodology. We collected the information through semi-structured interviews and open-ended written questionnaires. We analyzed data using an inductive system of categories and codes. Three topics were addressed in the results: profile of academics acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
1
12
0
3
Order By: Relevance
“…The resistance of faculty, for instance, is also explored by scholars (Anstead, 2016). Even if the framework has triggered interest in the arena of student affairs well beyond accessibility (Houghton & Fovet, 2012), instructors remain overall more cautious (Harrison, 2006;Moriña et al, 2020). Instructors indeed can fear that UDL will increase their workload; they at times mistakenly assume UDL implementation requires technological expertise; they can be affected by misperceptions that lead them to think UDL affects academic standards and integrity (Anstead, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The resistance of faculty, for instance, is also explored by scholars (Anstead, 2016). Even if the framework has triggered interest in the arena of student affairs well beyond accessibility (Houghton & Fovet, 2012), instructors remain overall more cautious (Harrison, 2006;Moriña et al, 2020). Instructors indeed can fear that UDL will increase their workload; they at times mistakenly assume UDL implementation requires technological expertise; they can be affected by misperceptions that lead them to think UDL affects academic standards and integrity (Anstead, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inclusive education tries to develop an approach to teaching and learning that is more flexible to meet different learning needs. If teaching becomes more effective as a result of the changes introduced by inclusive education, then all children will benefit (not just children with special needs) (Moriña, Perera, & Carballo, 2020).…”
Section: Inclusive Educationmentioning
confidence: 99%
“…Many studies have been conducted and have demonstrated the importance of training programs for teachers in the field of inclusive education, but the impact is not relevant. After participation, the teacher returns to the old methods and with the same attitude (Moriña et al, 2020). There is not much research on creating practice communities for middle school teachers from inclusive classes.…”
Section: Introductionmentioning
confidence: 99%